Composite material capable of improving magnetic exchange bias field and preparation method thereof

By loading g-C3N4 on the α-Fe2O3 nanowire to form porous nanocomposites, the problems of insufficient thermal stability and magnetic exchange bias field at low temperatures are solved, and a higher blocking temperature is achieved and coercive force improve the performance of magnetic recording media.

CN119152893APending Publication Date: 2024-12-17CHINA JILIANG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311247300.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing iron oxide exchange bias materials have insufficient thermal stability and magnetic exchange bias field performance at low temperatures, making it difficult to meet the needs of high-performance magnetic recording media.

Method used

Design a porous nanocomposite material to form an α-Fe2O3/g-C3N4 composite material by loading g-C3N4 on ordered α-Fe2O3 nanowires, and adjusting the exchange bias effect using g-C3N4 to increase surface disorder Rotate to increase the blocking temperature and coercivity.

Benefits of technology

The blocking temperature, coercive force and exchange bias field of the composite material are significantly improved, and its thermal stability and magnetic properties are enhanced, making it have better application prospects in magnetic recording media.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119152893A_ABST
    Figure CN119152893A_ABST
Patent Text Reader

Abstract

The invention aims to design a composite material capable of improving a magnetic exchange bias field. The material is a porous nano alpha-Fe2O3 / g-C3N4 composite material capable of improving the magnetic exchange bias field, which is synthesized by loading g-C3N4 on an ordered alpha-Fe2O3 nanowire. The method is simple to operate, environment-friendly and low in energy consumption; the porous nano composite material prepared by the method has a relatively high specific surface area, and meanwhile, the composite material has more surface disordered spinning, so that the blocking temperature and coercive force of the composite material are improved, the exchange bias field of the composite material is improved, and the composite material has a relatively good practical utilization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of magnetic recording materials, and in particular to a composite material capable of improving a magnetic exchange bias field and a preparation method thereof. Background Art

[0002] Since the exchange bias (EB) effect was first observed in Co / CoO nanoparticles by Meiklejohn and Bean in 1956, it has attracted extensive attention from researchers in the fields of basic research and technological applications. In ferromagnetic / antiferromagnetic systems, the typical manifestation of exchange bias is that in an external magnetic field, when cooled below the Neel temperature of the antiferromagnet, the hysteresis loop moves relative to the magnetic field axis and the coercivity increases. At present, exchange bias has become an important basis for information storage technology and has broad application prospects in spin valves, tunnel devices, magnetic recording media, magnetic sensors, etc. Specifically, exchange bias in magnetic nanostructures can be used for the pins of spin valve read heads and magnetic hard reference layers in MRAM storage circuits, as well as to enhance the thermal stability of small magnetic powders in advanced disk media.

[0003] As research continues to deepen, exchange bias effects have also been observed in some antiferromagnetic materials and antiferromagnetic oxides, such as cobalt oxide, γ-Fe2O3 and α-Fe2O3, which are caused by their disordered surface spins. Among them, hematite (α-Fe2O3) is below the Neel temperature until the Morin transition (T M = 263 K) exhibits weak ferromagnetism due to a slight spin tilt on the basal plane. M Below this temperature, the spin rotation and tilt disappear, and antiferromagnetic order appears. When the hematite particles become small enough, thermal agitation causes the magnetization direction of individual domains to fluctuate, resulting in a magnetic field at the blocking temperature T. b Above T, superparamagnetic behavior occurs, while at T b These magnetic moments are spatially frozen. Therefore, studying the exchange bias effect in α-Fe2O3 nanocrystals is an important research topic.

[0004] At present, the research on iron oxide exchange bias is mainly focused on core-shell structures and multilayer structures. If metal nanoparticles (NPs) are in contact with other materials, strong charge exchange can occur through the interface. At the same time, the interaction of NPs can be promoted or hindered by changing the morphology of the material and controlling the crystal phase and other conditions, thereby improving the magnetic properties of the composite material. Especially at the interface with C nanoparticles, the conduction electrons of C are coupled with the magnetic spins of metal atoms, and the interface of amorphous carbon is graphitized and antiferromagnetic. In addition, there is charge exchange at the interface between metal nanoparticles and graphitized carbon, which changes the magnetization of the interface and thus increases the magnetic exchange bias field of the system. Summary of the invention

[0005] The purpose of the present invention is to design a composite material capable of improving the magnetic exchange bias field. The material is prepared by loading g-C3N4 on ordered α-Fe2O3 nanowires to synthesize a porous nano α-Fe2O3 / g-C3N4 composite material capable of improving the magnetic exchange bias field. The porous nano composite material has a higher specific surface area and more surface disordered spins exist in the composite material, thereby improving its blocking temperature and coercive force and increasing its exchange bias field, so that the composite material has a better prospect for practical utilization.

[0006] A composite material capable of improving magnetic exchange bias field, characterized in that its preparation method comprises the following steps: A composite material capable of improving magnetic exchange bias field, characterized in that a porous nano-α-Fe2O3 / g-C3N4 composite material capable of improving magnetic exchange bias field is synthesized by loading g-C3N4 on ordered α-Fe2O3 nanowires, and the preparation method thereof comprises the following steps: (I) Preparation of α-Fe2O3: 1) Add SBA-15 and ferric nitrate in a ratio of Si:Fe=2:1 into a polytetrafluoroethylene beaker and add 90 ml of ethanol; 2) Ultrasonicate the mixed solution for 30 minutes, then stir at 50°C for 50 minutes until the ethanol solution evaporates and becomes powder. The ultrasonic frequency is 40±2kHz and the time is 0.5 hours; 3) Add 40 ml of n-hexane to the powder obtained in 2) and stir at 50°C until it is dry and powdery; 4) Pre-calcine the powder at 220°C for 2 hours at a heating rate of 1°C / min in a muffle furnace. Centrifuge the product at 5000-10000 r / min for 5 minutes, discard the supernatant, wash with anhydrous ethanol, and centrifuge, repeat twice, and dry the resulting precursor precipitate in a drying oven for 12 hours; 5) The dried precursor is placed in a muffle furnace and calcined at 650°C for 6 hours; 6) Remove the SBA-15 template twice with 100ml of 2mol / L concentrated NaOH solution in a 90℃ water bath, heating in the water bath for 1h the first time and 0.5h the second time. Centrifuge the product at 5000-10000 r / min for 5min, discard the supernatant, wash with anhydrous ethanol and centrifuge, repeat twice, and dry the obtained precursor precipitate in a drying oven for 12h; (II) Preparation of porous nano-α-Fe2O3 / g-C3N4: 1) 0.2 g of α-Fe2O3 was dispersed in 20 ml of deionized water. Then different volumes of g-C3N4 suspension were added to the α-Fe2O3 solution under magnetic stirring (400 rpm) to form a mixed solution. The mixed solution was then dispersed by ultrasound for 15 min and stirred for 10 h to form a precipitate. 2) The precipitate was washed with deionized water and dried. Finally, the sample was annealed at 550 °C for 5 h to obtain a porous nano-α-Fe2O3 / g-C3N4 composite material; 3) The obtained composite material was placed at 300K, 200K, 100K, 50K and 10 K to test the magnetic properties of the material under a magnetic field change from -5T to 5T, and the blocking temperature, coercive force and exchange bias field were obtained according to the hysteresis loop and ZFC-FC curve. The microscopic coercive force field distribution, interaction field distribution and magnetic domain data under a certain temperature environment were obtained according to FORC calculation.

[0007] The beneficial effects of the present invention are as follows: 1) The present invention is simple to operate, environmentally friendly and has low energy consumption; 2) The present invention utilizes the addition of g-C3N4 to adjust the magnitude of the exchange bias effect of the composite material; 3) By nano-sizing the iron oxide material and adding the composite material, more surface disordered spins are present, thereby improving its blocking temperature, coercive force and increasing its exchange bias field, so that the composite material has better practical utilization prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] In the following figures, α-Fe2O3, FCN-2, FCN-5 and FCN-10 are the sample numbers prepared in Example 1, Example 2, Example 3 and Example 4, respectively.

[0009] Figure 1 . TEM images of (a) α-Fe2O3 and (b) FCN-5; SEM images of (c) g-C3N4, (d) α-Fe2O3, (e) FCN-2, (f) FCN-5 and (g) FCN-10; (h), (i), (j) and (k) represent the distribution of C, N, O and Fe elements in FCN-5.

[0010] Figure 2 . (a) XRD patterns and (b) N2 adsorption–desorption isotherms of g-C3N4, α-Fe2O3, FCN-2, FCN-5, and FCN-10.

[0011] Figure 3. ZFC-FC curves of (a) α-Fe2O3, (b) FCN-2, (c) FCN-5 and (d) FCN-10; (e) hysteresis loops of α-Fe2O3, (f) FCN-2, (g) FCN-5 and (h) FCN-10; the inset shows the enlarged view of the low magnetic field region of the hysteresis loop.

[0012] Figure 4 . Magnetic parameters of α-Fe2O3, FCN-2, FCN-5 and FCN-10; H1, H2: left intercept and right intercept of the hysteresis line on the X axis when M = 0, |H c | = |(H1-H2) / 2| and |H EB | = |(H1+ H2) / 2|.

[0013] Figure 5 . Exchange bias H of α-Fe2O3, FCN-2, FCN-5 and FCN-10 at different temperatures EB and coercivity H c .

[0014] Figure 6 . FORC diagrams of (a) α-Fe2O3, (b) FCN-2, (c) FCN-5 and (d) FCN-10 at 10 K; FORC diagrams of (e) α-Fe2O3, (f) FCN-2, (g) FCN-5 and (h) FCN-10 at 100 K; FORC diagrams of (i) α-Fe2O3, (j) FCN-2, (k) FCN-5 and (o) FCN-10 at 300 K.

[0015] Figure 7 . Day-plots of α-Fe2O3, FCN-2, FCN-5 and FCN-10 at three test temperatures; for easy distinction, numbers 1 to 3 represent the temperatures of 10 K, 100 K and 300 K, respectively. The symbols in the figure represent superparamagnetism (SP), stable single domain (SD), pseudo single domain (PSD) and multi-domain (MD). DETAILED DESCRIPTION

[0016] The present invention is further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the present invention, but are not intended to limit the scope of the present invention. Example 1

[0017] 1) Add SBA-15 and ferric nitrate in a ratio of Si:Fe=2:1 into a polytetrafluoroethylene beaker and add 90 ml of ethanol; 2) Ultrasonicate the mixed solution for 30 minutes, then stir at 50°C for 50 minutes until the ethanol solution evaporates and becomes powder. The ultrasonic frequency is 40±2kHz and the time is 0.5 hours; 3) Add 40 ml of n-hexane to the powder obtained in 2) and stir at 50°C until it is dry and powdery; 4) Pre-calcine the powder at 220°C for 2 hours at a heating rate of 1°C / min in a muffle furnace. Centrifuge the product at 5000-10000 r / min for 5 minutes, discard the supernatant, wash with anhydrous ethanol, and centrifuge, repeat twice, and dry the resulting precursor precipitate in a drying oven for 12 hours; 5) The dried precursor is placed in a muffle furnace and calcined at 650°C for 6 hours; 6) Remove the SBA-15 template twice with 100 ml of 2 mol / L concentrated NaOH solution in a 90°C water bath, heating in the water bath for 1 hour the first time and 0.5 hour the second time. Centrifuge the product at 5000-10000 r / min for 5 minutes, discard the supernatant, wash with anhydrous ethanol, and centrifuge, repeat twice, and dry the resulting precursor precipitate in a drying oven for 12 hours.

[0018] The specific surface area of ​​pure α-Fe2O3 obtained in Example 1 is equal to 105.36 m 2 / g, the coercive force and exchange bias field measured at 10K temperature and 100Oe magnetic field are equal to 3280Oe and 720Oe respectively. Example 2

[0019] The steps for preparing pure α-Fe2O3 are the same as those in Example 1, with the addition of the following steps: 1) 0.2 g of pure α-Fe2O3 and g-C3N4 were dispersed in 20 ml of deionized water respectively. Then 2 ml of g-C3N4 suspension was added to the α-Fe2O3 solution under magnetic stirring (400 rpm) to form a mixed solution. The mixed solution was then dispersed by ultrasound for 15 min and stirred for 10 h to form a precipitate. 2) The precipitate was washed with deionized water and dried. Finally, the sample was annealed at 550 °C for 5 h.

[0020] The specific surface area of ​​the composite material obtained in Example 2 is equal to 69.26 m 2 / g, the coercive force and exchange bias field measured at 10K temperature and 100Oe magnetic field are equal to 4637Oe and 708Oe respectively. Example 3

[0021] The steps for preparing pure α-Fe2O3 are the same as those in Example 1, with the addition of the following steps: 1) 0.2 g of pure α-Fe2O3 and g-C3N4 were dispersed in 20 ml of deionized water respectively. Then 5 ml of g-C3N4 suspension was added to the α-Fe2O3 solution under magnetic stirring (400 rpm) to form a mixed solution. The mixed solution was then dispersed by ultrasound for 15 min and stirred for 10 h to form a precipitate. 2) The precipitate was washed with deionized water and dried. Finally, the sample was annealed at 550 °C for 5 h.

[0022] The specific surface area of ​​the composite material obtained in Example 3 is equal to 65.13 m 2 / g, the coercive force and exchange bias field measured at 10K temperature and 100Oe magnetic field are equal to 4700Oe and 794Oe respectively. Example 4

[0023] The steps for preparing pure α-Fe2O3 are the same as those in Example 1, with the addition of the following steps: 1) 0.2 g of pure α-Fe2O3 and g-C3N4 were dispersed in 20 ml of deionized water respectively. Then 10 ml of g-C3N4 suspension was added to the α-Fe2O3 solution under magnetic stirring (400 rpm) to form a mixed solution. The mixed solution was then dispersed by ultrasound for 15 min and stirred for 10 h to form a precipitate. 2) The precipitate was washed with deionized water and dried. Finally, the sample was annealed at 550 °C for 5 h.

[0024] The specific surface area of ​​the composite material obtained in Example 4 is equal to 60.59 m 2 / g, the coercive force and exchange bias field measured at 10K temperature and 100Oe magnetic field are equal to 4400.5Oe and 714.5Oe respectively.

[0025] Characterization of the composite materials.

[0026] 1. Scanning and transmission electron microscopy characterization of Examples 1-4, such as Figure 1 , the results show that: Figure 1(a) shows the prepared α-Fe2O3 nanowire structure, while Figure 1(b) shows the layered structure of g-C3N4, which is the substrate for loading α-Fe2O3 nanowires.

[0027] Second, XRD characterization of the product, such as Figure 2As shown, the results show that the two obvious diffraction peaks of pure g-C3N4 appear at 12.86° and 27.50°, respectively, which can be attributed to the (100) and (002) crystal planes, indicating the stacking of conjugated aromatic rings. The characteristic peaks of pure α-Fe2O3 nanowires and composite samples are very consistent with the characteristic peaks corresponding to the α-Fe2O3 standard card with space group R-3c, without any extra peaks.

[0028] 3. Perform VSM test on examples 1-4 and calculate T by testing ZFC-FC curve b Blocking temperature, test the hysteresis loop and calculate the coercive force and exchange bias field, the coercive force and exchange bias field of Examples 1-3 in the 100Oe magnetic field range, such as Figure 3 , Figure 4 , Figure 5 As shown. The zero-field cooling and field cooling magnetization of the sample bifurcate at a certain temperature, and a broad peak appears on the zero-field cooling curve, which shows the characteristic behavior of the interacting nanoparticle system. Compared with pure α-Fe2O3, the blocking temperature T b The ZFC curve shifts to higher temperature, and the peak value in the ZFC curve also expands. This indicates that the effective energy barrier of the system increases, which is related to the interaction within the nanoparticle system. The decrease in the magnetic susceptibility of the composite material at 5T is due to the structural disorder caused by the addition of the non-magnetic component g-C3N4. The coercivity (H c ) and the exchange bias field (H EB ) increase with decreasing temperature. c In comparison, H EB With the increase of g-C3N4 content, H EB It also showed a trend of first increasing and then decreasing. The H EB The highest is 794Oe.

[0029] Fourth, the first-order inversion curve analysis was used for Example 1-4, and a Day chart was drawn, such as Figure 6 , Figure 7 The FORC peak of pure α-Fe2O3 is located near the origin and along the H c Axis extension, along H u The distribution along the H axis is small, which is similar to the FORC distribution of superparamagnetic (SP) particles. Compared with pure α-Fe2O3, the FORC peak of the composite sample is located outside the low coercive force field source region. u Axis extension, along H cThe smaller axis distribution indicates that the composite sample has a typical FORC distribution of single-domain superparamagnetic (SD+SP) particles with a larger interaction field. As the FORC test temperature changes, the Day diagram shows an obvious transition, that is, the FORC domains of the four samples change from a superparamagnetic single domain (SP-SD) mixed morphology at high temperature to a pseudo single domain and single domain (SD) mixed morphology at low temperature, especially for FCN-5 at 10 K.

Claims

1. A composite material capable of improving magnetic exchange bias field, characterized in that: A porous nano-α-Fe2O3 / g-C3N4 composite material capable of improving the magnetic exchange bias field is synthesized by loading g-C3N4 on ordered α-Fe2O3 nanowires. The preparation method comprises the following steps: (I) Preparation of α-Fe2O3: 1) Add SBA-15 and ferric nitrate in a ratio of Si:Fe=2:1 into a polytetrafluoroethylene beaker and add 90 ml of ethanol; 2) The mixed solution was ultrasonicated for 30 min, and then stirred at 50 °C for 50 min until the ethanol solution evaporated into powder. The ultrasonic frequency was 40 ± 2 kHz and the time was 0.5 h. 3) Add 40 ml of n-hexane to the powder obtained in 2) and stir at 50°C until it is dry and powdery; 4) Pre-calcine the powder at 220°C for 2 hours at a heating rate of 1°C / min in a muffle furnace, centrifuge the product at 5000-10000 r / min for 5 minutes, discard the supernatant, wash with anhydrous ethanol and centrifuge, repeat twice, and dry the obtained precursor precipitate in a drying oven for 12 hours; 5) The dried precursor is placed in a muffle furnace and calcined at 650°C for 6 hours; 6) Remove the SBA-15 template twice with 100 ml of 2 mol / L concentrated NaOH solution in a 90°C water bath. Heat in a water bath for 1 h the first time and for 0.5 h the second time. Centrifuge the product at 5000-10000 r / min for 5 min. Discard the supernatant and wash with anhydrous ethanol and centrifuge. Repeat twice. Dry the resulting precursor precipitate in a drying oven for 12 h. (II) Preparation of porous nano-α-Fe2O3 / g-C3N4: 1) 0.2 g of α-Fe2O3 was dispersed in 20 mL of deionized water, and then different volumes of g-C3N4 suspension were added to the α-Fe2O3 solution under magnetic stirring (400 rpm) to form a mixed solution. The mixed solution was then dispersed by ultrasound for 15 min and stirred for 10 h to form a precipitate. 2) The precipitate was washed with deionized water and dried, and finally the sample was annealed at 550 °C for 5 h to obtain a porous nano-α-Fe2O3 / g-C3N4 composite material; 3) The obtained composite materials were placed at 300K, 200K, 100K, 50K and 10 K to test the magnetic properties of the materials under a magnetic field varying from -5T to 5T. The blocking temperature, coercive force and exchange bias field were obtained based on the hysteresis loop and ZFC-FC curve. The microscopic coercive force field distribution, interaction field distribution and magnetic domain data under a certain temperature environment were obtained based on FORC calculation.

Citation Information

Cited By

  • Preparation method of Ni / Fe3O4 composite nano three-dimensional array strain sensor based on tunneling effect and sensor

    CN119826676A